Pendekatan Scientific Approach dalam Mengembangkan Alat Praktikum IPA Terintegrasi Lingkungan untuk Meningkatkan Keterampilan dan Kreativitas Guru IPA - Khaerus Syahidi; Laxmi Zahara; Nunung Ariandani; Ria Hastiarna (Universitas Hamzanwadi, 2019)
This PkM program aims to improve: (1) teacher skills in designing and developing KIT of Natural Sciences practicum tools, Practical tools, laboratory management SOP as well as integrated science materials with the potential of the surrounding environment. The method used in achieving these objectives is the implementation of inservice in the form of training and assistance. The training carried out is a training to develop the skills and creativity of science teachers in the production / design of an integrated natural science practicum device based on the environment and training to design learning using a scientific approach that utilizes the KIT of science that has been produced. Assistance is also carried out related to improving the ability of teachers to explore, elaborate and reflect on integrated science teaching materials. The output of this activity is in the form of KIT of integrated environment-based practicum tools equipped with SOP for the management of practicum with environmental conditions; Integrated practicum tools in integrated science learning (RPP, LKS, teacher's guide) to support scientific approach learning; Integrated science laboratory management SOP; Refresher teaching materials integrated science materials; Scientific article (national publication). The results of the activities that have been achieved include, increased understanding and skills of natural science teachers in the Jerowaru SMPN 1 Natural Science teacher group on integrated science material, increasing teachers' understanding of learning with an inquiry approach, increasing the skills of science teachers designing / making KIT Simple science made from raw materials from the surrounding environment to support science learning using the inquiry discovery approach (scientific approach), increasing the ability of science teachers to design learning tools with the inquiry inquiry approach (scientific approach), training the skills and abilities of science teachers in partner schools in implementing science learning with inquiry discovery (scientific approach) approach.